Performance of FACTS Devices for Power System Stability - Bhupendra Sehgal; S P Bihari; Yogita Kumari; R.N. Chaubey; Anmol Gupta (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
When a power grid is connected to an induction type wind electric generator (WEG), when there is variation in load and wind speed, grid voltage also vary. In this paper, we study what is the impact when there is a variation of load and wind by variation of real power and reactive power consumed by WEG effect of load and wind speed variations on real power supplied and reactive power consumed by the WEG as well as voltage on the grid are studied. The voltage variation in the grid is controlled by reactive power compensation using shunt connected Static VAR Compensator (SVC) comprising Thyristor Controlled Reactor (TCR) and Fixed Capacitor (FC). With the help of Fuzzy Logic Controller (FLC), TCR is operated automatically.